Optimasi Biaya Pengendalian Persediaan Alat Suntik (Spuit) Dengan Metode Optimisasi Robust Menggunakan Aplikasi Python Di RSUD Dr. Pirngadi - Rotua Ignasia Saragih; Tri Andri Hutapea (Lembaga Pengembangan Kinerja Dosen, 2023)
Inventory control is very important for companies because without proper inventory control the company will experience problems in meeting consumer needs both in the form of goods and services produced by the company. RSUD Dr. Pirngadi is one of the companies that uses conventional methods to calculate the total cost of inventory so that the costs incurred both for ordering syringes and storage costs are still high, therefore it is necessary to control the inventory of syringes which aims to minimise inventory costs so that company goals can be achieved. In solving the problem of controlling inventory costs to minimise total inventory costs, namely using robust optimisation. Robust optimisation is an optimisation model that contains uncertainty data to obtain the right solution using linear program solving. The results of research at the RSUD Dr. Pirngadi obtained the total cost of inventory according to company policy for the use of 3 mL Terumo syringes is Rp.426,104,665 while the robust optimisation method is Rp.319,647,106 so it can be concluded that by applying the robust optimisation method to the company can save inventory costs of Rp.106,987,599 or 25%. Furthermore, the total inventory cost of using a 5 mL Terumo syringe according to company policy is Rp.208,402,454 while the robust optimisation method is Rp.166,608,139 so it can be concluded that by applying the robust optimisation method to the company can save inventory costs of Rp.41,794,315 or 20%.